Peran Emotion Based Attachment Ter-hadap Brand Loyalty dengan Customer Experience sebagai Pemoderasi - Trifiyanto, Kabul (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2024)
This research has proven the influence of emotion based attachment (brand love, brand passion, and brand pride) on brand loyalty with customer experience as a moderating variable. A total of modern café in Kebumen contributed to filling out the questionnaire. Purposive sampling was used by determining the criteria for respondents, namely those aged between 17 and more than 40 years and who had made purchases more than once. SmartPLS 3 SEM is used to process data. The research results showed that brand loyalty was directly influenced only by brand passion and brand pride, but not by brand love. Customer experience cannot moderate the influence of brand loyalty and brand passion on brand loyalty. However, customer experience can moderate the relationship between brand pride and brand loyalty. In conclusion, positive emotional attachment occurs in brand loyalty, especially through a sense of pride in the brand, which plays an important role in influencing brand loyalty. Positive customer experience can also increase the influence of brand pride on brand loyalty. Therefore, brand managers need to pay attention to efforts to improve the quality of customer experience and strengthen brand passion and brand pride as a strategy to maintain and increase existing brand loyalty.